Timing of the Infancy-Childhood Growth Transition in Rural Gambia - Bernstein, Robin M.; O'Connor, G. Kesler; Vance, Eric A.; Affara, Nabeel; Drammeh, Saikou; Dunger, David B.; Faal, Abdoulie; Ong, Ken K.; Sosseh, Fatou; Prentice, Andrew M.; Moore, Sophie E. (Frontiers in Endocrinology, 2020)
The Karlberg model of human growth describes the infancy, childhood, and puberty (ICP) stages of human growth as continuous and overlapping, and defined by transitions driven by sequential additional effects of several endocrine factors that shape the growth trajectory and resultant adult size. Previous research has suggested that a delayed transition from the infancy to the childhood growth stage contributes to sub-optimal growth outcomes. A new method developed to analyze the structure of centile crossing in early life has emerged as a potential tool for identifying the ICT, through quantifying patterns of adjacent monthly weight-for-age z-score (WAZ) deviation correlations. Using this method, the infancy-childhood transition was identified as taking place at around 12 months of age in two cohorts of UK infants. Here, we apply this method to data collected as part of a longitudinal growth study in rural Gambia (the Hormonal Regulators of Growth, or HERO-G study, N=212 (F=99, M=113)), in order to identify the ICT and assess whether timing of this transition differs across groups based on sex or birth seasonality. We calculated Pearson correlation coefficients for adjacent monthly WAZ score deviations. Based on the patterns of change in the correlation structure over time, our results suggest that the infancy-childhood transition occurs at around 9 months of age in rural Gambian infants. This points to an accelerated ICT compared to UK infants, rather than a delayed ICT. A comparatively later transition, seen in UK infants, allows maximal extension of the high rates of growth during the infancy stage; an earlier transition as seen in Gambian infants cuts short this period of rapid growth, potentially impacting on growth outcomes in childhood while diverting energy into other processes critical to responses to acute infectious challenges. Growth in later developmental stages in this population offers an extended window for catch-up growth.